Do local currency bond markets enhance financial stability? - Donghyun Park; Kwanho Shin; Shu Tian (Asian Development Bank (ADB), 2018)
It is widely believed that local currency bond markets (LCBMs) can promote financial stability in developing countries. For instance, they can help mitigate the currency and maturity mismatch that contributed to the outbreak of the Asian financial crisis of 1997-1998. In this paper, we empirically test such conventional wisdom on the stabilizing effect of LCBMs. To do so, we analyze and compare the financial vulnerability of developing countries during two episodes of financial stress - global financial crisis and taper tantrum. During the two episodes, we find a negative association between the growth of LCBMs and the degree of currency depreciation in emerging economies. Similar association is found of bank loans but not for the stock market.
Keywords: E44; F34; F38; F42; F62; 330; Asian financial crisis; bonds; currency mismatch; developing countries; financial stability; local currency bond markets; maturity mismatch